2018
DOI: 10.1186/s12992-018-0358-5
|View full text |Cite
|
Sign up to set email alerts
|

Using qualitative and community-based engagement approaches to gain access and to develop a culturally appropriate STI prevention intervention for foreign female entertainment workers in Singapore

Abstract: BackgroundThere is an increasing global movement of foreign female entertainment workers (FEWs), a hard-to-reach population vulnerable to HIV/STIs. This paper described the needs assessment phase before intervention implementation where the socio-organisation, sexual risk behaviours and access to health services of foreign FEWs in Singapore were explored. We also highlighted how qualitative inquiry, census enumeration technique and community-based engagement approaches were used to gain access and to develop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Our results identified an encouraging trend underscoring the importance of facilitators that operate on a community organisation level. In congruence with previous literature [17,[57][58][59], our findings strongly imply that collective agency of the Ukrainian FSW community via NGO membership largely facilitated access to the basic PP, as most PP recipients were clients of an NGO. Knowledge of HIV transmission routes was higher amongst PP recipients across all years, which may be attributable to consultations with social workers and the distribution of HIV awareness-raising materials, two components that were consistently included in the PP.…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…Our results identified an encouraging trend underscoring the importance of facilitators that operate on a community organisation level. In congruence with previous literature [17,[57][58][59], our findings strongly imply that collective agency of the Ukrainian FSW community via NGO membership largely facilitated access to the basic PP, as most PP recipients were clients of an NGO. Knowledge of HIV transmission routes was higher amongst PP recipients across all years, which may be attributable to consultations with social workers and the distribution of HIV awareness-raising materials, two components that were consistently included in the PP.…”
Section: Plos Onesupporting
confidence: 90%
“…We observed a high level of stigma (54%) amongst PP recipients who feared their HIV status being exposed in 2009, however we did not observe meaningful between-group differences. Previous studies have deemed stigma to be one of the most salient barriers to HIV prevention [17,52,53], fuelled by other factors on different structural levels such as criminalisation [15,[54][55][56] on the macrostructural level and a lack of community empowerment on the community organisational level [17,57,58].…”
Section: Plos Onementioning
confidence: 99%
“…We observed a high level of stigma (54%) amongst PP recipients who feared their HIV status being exposed in 2009, however we did not observe meaningful between-group differences. Previous studies have deemed stigma to be one of the most salient barriers to HIV prevention [17, 52, 53], fuelled by other factors on different structural levels such as criminalisation [15, 54-56] on the macrostructural level and a lack of community empowerment on the community organisational level [17, 57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies revealed economic marginalization (i.e. accepting increased pay for unprotected sex) [40,46] (Box 5, Supplementary Digital Content, http:// links.lww.com/QAD/C119), language barriers [41], and fear of police using condoms as evidence [29,41] as macrostructural barriers to condom negotiation and use. In work venues, gaps in condom availability [29], client/aggressor violence [46], and stealthy condom removal by clients [31,41,51] posed pervasive barriers to condom use.…”
Section: Key Structural Determinantsmentioning
confidence: 99%